2019
DOI: 10.1111/jog.14072
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence rate and associated factors of borderline ovarian tumors in the south of Vietnam

Abstract: Aim This study aimed to determine the recurrence rate and related risk factors of borderline ovarian tumors (BOT). Methods We conducted a retrospective cohort study with 433 patients who were surgically treated for primary BOT at Tu Du Hospital from 11/2008 to 09/2015. We used the life table method to estimate the cumulative recurrence rate. We used the log–rank test and Cox proportional hazard model to determine recurrence‐associated factors. Results Median follow‐up time was 43 months (range: 3–105 months). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In our study, and as expected, an advanced FIGO stage was found to be a risk factor for recurrence of BOT after conservative surgery. This result is consistent with the literature, as many authors have shown that advanced FIGO stage (≥II) was a factor in recurrence risk and decreased recurrence-free survival after conservative treatment, even in the case of complete surgery [15,16,19,28,37,43,48,49]. The presence of implants was also a risk factor for recurrence of BOT in multivariate analysis.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, and as expected, an advanced FIGO stage was found to be a risk factor for recurrence of BOT after conservative surgery. This result is consistent with the literature, as many authors have shown that advanced FIGO stage (≥II) was a factor in recurrence risk and decreased recurrence-free survival after conservative treatment, even in the case of complete surgery [15,16,19,28,37,43,48,49]. The presence of implants was also a risk factor for recurrence of BOT in multivariate analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Referring patients to an oncology center may allow us to optimize their management. Fauvet et al (27) Fauvet et al (18) Romagnolo et al (30)) Fauvet et al (10) Park et al (22) Zapardiel et al (31) Ewald-Riegler et al (23) Azuar et al (26) Bendifallah et al (9) Bendifallah et al (32) Helpman et al (19) Ouldamer et al (20) Delle Marchette et al (24) Vo et al (25) 2004…”
Section: Discussionmentioning
confidence: 99%